2008
DOI: 10.1136/gut.2008.157735
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome increases the risk of liver cirrhosis in chronic hepatitis B

Abstract: Metabolic syndrome is an independent risk factor of liver cirrhosis in CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
185
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 42 publications
7
185
0
1
Order By: Relevance
“…In particular, metabolic factors, including DM and hypertension, were also significantly associated with higher rates of primary adverse outcomes, although DM was not shown to be an independent variable on multivariate analysis. Currently, there are limited data regarding the relationship between chronic HBV infection and metabolic factors (29,30). Wong et al (29) demonstrated that coincidental metabolic syndrome in CHB patients increased the risk of liver fibrosis progression, independent of viral load and hepatitis activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, metabolic factors, including DM and hypertension, were also significantly associated with higher rates of primary adverse outcomes, although DM was not shown to be an independent variable on multivariate analysis. Currently, there are limited data regarding the relationship between chronic HBV infection and metabolic factors (29,30). Wong et al (29) demonstrated that coincidental metabolic syndrome in CHB patients increased the risk of liver fibrosis progression, independent of viral load and hepatitis activity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are limited data regarding the relationship between chronic HBV infection and metabolic factors (29,30). Wong et al (29) demonstrated that coincidental metabolic syndrome in CHB patients increased the risk of liver fibrosis progression, independent of viral load and hepatitis activity. Another study showed that metabolic factor-related hepatic steatosis was significantly associated with antiviral treatment failure in CHB patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that pre-existing metabolic syndrome, as defined by the 2001 US NCEP-ATP III criteria, confered a statistically significant 2.13 and 1.56 fold increased risk for terminal liver diseases as HCC and ICC which was independent of other risk factors [33]. Recent data from Chinese and Korean cohorts established that MS is a risk factor of advanced liver fibrosis and cirrhosis independent of viral factors in chronic HBV infection [34,35].…”
Section: Host Related Factors Virus Related Factors Additional Factorsmentioning
confidence: 85%
“…Although LC has been shown to be associated with the occurrence of GERD, the underlying mechanisms which link both diseases together remained largely unknown. Metabolic syndrome, diabetes mellitus and obesity are known risk factors of LC development [23]. Of particular note is that diabetes mellitus, metabolic syndrome and obesity could also increase the risk of GERD [2].…”
Section: Discussionmentioning
confidence: 99%